NILAI SIKAP ILMIAH KERJA SAMA DALAM ANIME “DR. STONE: RYUSUI” UNTUK PENGUATAN PENDIDIKAN KARAKTER ANAK: Penelitian Kualitatif - Muhammad Alfin Numan; Fina Fakhriyah; Gunawan Setiadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to analyze the values of scientific collaboration found in the animated film "Dr. Stone: Ryusui" for the enhancement of children's character education. The study uses qualitative research method with content analysis. Data collection techniques include observation, documentation, and content analysis. The data sources consist of primary data from the anime "Dr. Stone: Ryusui" and secondary data from books, journals, and articles. The results of the study show that there are scientific collaborative attitudes in the anime film "Dr. Stone: Ryusui," namely: 1) Willingness to take responsibility. 2) Willingness to help friends. 3) Respect for others' opinions. 4) Mutual contribution of both effort and ideas. These values of scientific collaborative attitudes in the anime film "Dr. Stone: Ryusui" can be used to strengthen character education for children, particularly in the values of mutual cooperation and integrity.